2019
DOI: 10.1016/j.jsv.2019.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Generating controlled localized stimulations on haptic displays by modal superimposition

Abstract: In the field of tactile feedback, researchers try to generate localized stimulations on screens. Some solutions such as time reversal or phased array use vibration induced in the screen equipped with piezoelectric ceramics. We propose to use the modal basis to reproduce a specified velocity field on such devices. We explain the theory and propose a methodology to practically synthesize the voltages to achieved a controlled focusing in a given time. Experiments on a simple demonstrator are in good agreement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…It can be observed that they participate unevenly and therefore the decomposition can be pruned to retain only eight modes. To do this the τ criterion defined in [13] is adapted. Denoting E the subset of selected modes (dim E = 8), the criterion is written for the set of modes (cf Fig.…”
Section: Electronicmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that they participate unevenly and therefore the decomposition can be pruned to retain only eight modes. To do this the τ criterion defined in [13] is adapted. Denoting E the subset of selected modes (dim E = 8), the criterion is written for the set of modes (cf Fig.…”
Section: Electronicmentioning
confidence: 99%
“…For instance, in a bi-modal Atomic Force Microscopy, a first bending mode is used for topography imaging and a second one gives mechanical and electromagnetic properties of a studied sample [11]. In other applications, more than one vibration mode are excited, as to produce travelling waves for ultrasonic motor [12], it is also used for haptic interface to produce localized stimulation by modal superposition [13]. In energy harvester, the multimodal approach [14,15] increases the efficiency of the system to extract more power, compared to a single degree of freedom harvester.…”
Section: Introductionmentioning
confidence: 99%
“…Localized vibrations in the 200-300 Hz range are reported to be achieved using a generalized adversarial network (GAN) to generate time-reversed signals [24]. Superimposition of vibration modes can also lead to localized vibrotactile feedback on large touch surfaces [25], [26]. Except [20], almost all the existing methods of localized vibrotactile rendering require many actuators.…”
Section: Introductionmentioning
confidence: 99%
“…They conducted a user study to demonstrate their capability to provide perceivable localized tactile feedback. Enferad et al [6] used the time-reversal method to produce velocity fields on touch surfaces using piezoelectric patches. They calculated the required voltage and dispatched them among piezo elements to produce localized tactile feedback by modal superposition.…”
Section: Introductionmentioning
confidence: 99%